استخدام بعض مظاهر الشروط المعرفية بين الرجال والنساء العرب (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present paper focuses on a very rich and complex area of grammar related to epistemic modals. It endeavors to account for the differences in occurrence of certain epistemic modal forms in the speech of Jordanian men and women. Some researchers maintain that epistemic forms signal women's lack of confidence and assertiveness. The present author found that some epistemic forms had higher frequency in men's speech to which the above account cannot be accurate. Men were found using more of `I think' and I mean' and as such forms are associated with the first person singular pronoun, they indicate that men care more about the clarification of their speech and could also reveal their superior social status. However, other epistemic forms that women use express their social status. It was also found that some epistemic words are used for decoration of one's style of speech, in the sense of adding variety to one's speech. يهدف هذا البحث إلى دراسة ظاهرة لغوية بepistemic modality حيث أظهرت الدراسات اللغوية وجود فرق كبير بين الرجال والنساء في استخدام هذه الأشكال اللغوية, واستخدم الباحث المنهج الكمي والكيفي لجمع معلوماته وتحليلها وتفسيرها, وصنف الأوضاع اللغوية إلى ثلاثة أوضاع حتى يمكن التعرف على زمان ومكان استخدام هذه الأشكال اللغوية. واستخلص الباحث أن كلا من الرجال والنساء يستخدم epistemic modality مع وجود فرق في درجة وعدد هذه الأشكال, وتوصل أيضاً إلى أن استخدام هذه الأشكال اللغوية مرتبط بعوامل اجتماعية مثل الجنس وموضوع الحديث والوضع الاجتماعي . ولاحظ الباحث أيضاً وجود تفاوت في عدد هذه الأشكال اللغوية بين الرجال والنساء, وتبين أن استخدام هذه الأشكال اللغوية يمكن أن يضيف نوعا من الجدة أو التغيير في أسلوب الحديث .